THE EFFECT OF BID-ASK SPREAD, MARKET VALUE, VARIANCE RETURN, DIVIDEND PAYOUT RATIO AND INFLATION ON HOLDING PERIOD - Trisandi Eka Putri; Icih Icih; Nisa Halimatusyadiah (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2021)
This study aimed to analyze the effect of the bid-ask spread, market value, variance return, dividend payout ratio, and inflation on the holding period. The population in this study are LQ45 and Non LQ45 companies listed on the Indonesia Stock Exchange in 2018-2020. Based on the sample criteria, there were 30 companies for LQ45 companies and 116 companies for Non LQ45 companies. The results showed that the bid-ask spread, market value, dividend payout ratio, and inflation had a significant positive effect on the holding period for both LQ45 and non-LQ45 companies. While the Variant return variable has a different effect, wherein the LQ45 company the return variance variable has no effect on the holding period while in the Non-LQ45 company the return variance variable has a significant negative effect on the holding period.